Multi-proxy reconstructions of productivity during the late Miocene - Xinying Wu; Yue Hu; Jingbo Nan; Weiqi Yao (PANGAEA, 2024)
The Late Miocene Biogenic Bloom (LMBB), marked by notable increases in biogenic components in marine sediments, provides insights into the response of the biological pump to climate change. However, understanding the timing, distribution, and cause of the LMBB remains limited. We use marine barite, a refractory mineral precipitating from the water column associated with carbon export, and other proxies (bio-SiO2 MAR, CaCO3 MAR) to reconstruct productivity in the equatorial Indian Ocean and equatorial western Atlantic between 12 and 5 Ma. At the same time, we compiled bio-SiO2 MAR data from 21 sites in the global ocean during the late Miocene. Multi-proxy records reveal the onset of the LMBB in the equatorial Indian Ocean at ~9 Ma, primarily driven by more vigorous upwelling during global cooling. We suggest that the steepened meridional temperature gradient and the Antarctic ice sheet expansion have strengthened ocean overturning, facilitating nutrient supply and biogenic bloom in upwelling regions.